Family Health Care Function is Related to Self-Care Management in Elderly with Hypertension - Irwina Angelia Silvanasari; Nurul Maurida; Trisna Vitaliati; Achmad Ali Basri (Sean Institute, 2025)
Hypertension is a global health problem in the elderly population. The family has a role in self-care for elderly people who are vulnerable to health problems. The aim of this research is to analyze the relationship between family health care functions and self-care management in elderly people with hypertension. This research is quantitative research. The sample size was 150 elderly people with hypertension using a sampling technique, namely simple random sampling. The variables studied were family health care function and hypertension self-care management. The chi square test was used as a bivariate analysis in this study. The research results found that the majority (57.3%) had good family health care functions, the majority (54%) had poor self-care management. Family health care function is related to self-care management in elderly people with hypertension with p value = 0.000 < 0.05%. Most elderly people with hypertension who have good family health care functions have good self-care management. Families should maximize their role regarding the implementation of family health care functions to be able to maximize good self-care management for family members who suffer from hypertension.